"Let Me Be Direct": Using Direct Assessments With Student Leaders. Issue 6 (8th February 2013) - Lindsay, Nathan; Hourigan, Aimee; Smist, Jennifer; Wray, Larry
Abstract Nathan Lindsay, Aimee Hourigan, Jennifer Smist, and Larry Wray discuss the benefits of direct assessment of student learning in a variety of co‐curricular programs.